Psychiatric emergencies in children and adolescents: Relationship between clinical and demographic characteristics. - Osorio-Martínez, Miriam (2017)
Introduction: Nowadays the presentation of acute psychiatric disorders is common in children and adolescents. Objective: To find the relationship between clinical and demographic variables of children and adolescents seen in the psychiatric emergency room. Design: Quantitative, observational, retrospective and analytical study. Setting: Hermilio Valdizán Hospital, Lima, Peru. Participants: Patients under 18 years (N = 285), both sexes, seen from September 2014 - September 2015. Interventions: Information was collected from medical records and classified into clinical and demographic variables. Univariate analysis was performed by frequency distribution and bivariate analysis by Chi square and Fisher exact tests. Results: 13% of all psychiatric emergencies were pediatric. These were more frequent in the female sex (60%), in the 12 to 17 age group (93.3%) and in the Lima Este origin group (73%). Mean age was 14.8 years (SD = 2.1). Aggressiveness (28.4%), hallucinations (13.7%), irritability (11.9%) and self-aggressiveness (10.9%) were the most frequent chief complaints. Suicidal ideation (9.1%) was associated with the female group OR 3.05 (IC-95%: 1.12- 8.35; p=0.023). F20-F29 (31.6%), F30-F39 (25.6%), and F60-F69 (18.6%) were the most frequent diagnostic categories. F30-F39 OR 2.31 (IC-95%: 1.28-4.16; p=0.005) and F60-F69 OR 2.11 (IC-95%: 1.09-4.10; p= 0.025) were associated with the female group. 49% of patients required hospitalization. Conclusions: There were a higher incidence and a lower age of presentation compared with previous years. Aggressiveness was the most frequent chief complaint. The female group had a higher risk of suicidal ideation, mood and personality disorders. The development of standardized protocols and specialized management is suggested.